Analisis Produktivitas Tenaga Kerja Terhadap Biaya Dan Waktu Pelaksanaan Pada Pekerjaan Pembangunan Proyek DPT Sungai Watudakon Mojokerto - Bagas Ramadhani; Wateno Oetomo (Jurnal Sipil Terapan, 2023)
The purpose of this study is to determine labor productivity against costs and time of implementation of the Watudakon River DPT project development work. The results of this study are the large number of labor productivity in the construction work of the Watudakon River DPT project, Mojokerto. With the results of calculating the overall productivity level, namely with an average of 2,228 m³/day, assuming 25% of formwork material shunting work and 75% installation of formwork, the calculation data is in accordance with what is carried out in the field. Duration of implementation according to a survey conducted on DPT Sungai Watudakon construction work, Mojokerto with an average value of duration for installation of pile cap formwork 1.013 days/hour, and for installation of DPT wall formwork 1.00 days/hour, then for pile repair work DPT cap and wall 1.00 days/hour, and also for pile cap casting work 1.166 days/hour, for DPT wall casting work 1.312 days/hour. The conclusion in this study is that the productivity of the workforce working hours is in accordance with the realization in the field and that work results can be increased by adding working hours or overtime.